Crab-Rangoons in Kyrat: (Re)Writing South-Asian History in Far Cry 4 - Mukherjee, Souvik (Games and Culture, 2021)
Recent research has started focusing on the representation of history in videogames. Such representation is almost always of mainstream history and usually presented from a Western perspective. Set in a fictitious Himalayan kingdom in South Asia, Ubisoft’s Far Cry 4 is arguably a crucial example of how history is represented using Western and even colonial frameworks and where the narratives that do not emerge from conventional written history are almost always rendered invisible. Using the frameworks of Subaltern Studies and “border-thinking,” this essay attempts to unpack issues of Orientalism and “colonial difference”; it then engages with postcolonial digital humanities and postcolonial game studies to comment on how history is represented in videogames and how the neglected gaps and silences in the game are important in constructing the historiography in videogames. In the process, the essay engages in a debate with current notions of videogame-historiography.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Playing Subaltern: Video Games and Postcolonialism - Mukherjee, Souvik (Games and Culture, 2018)
The postcolonial has still remained on the margins of Game Studies, which has now incorporated at length, contemporary debates of race, gender, and other areas that challenge the canon. It is difficult to believe, however, that it has not defined the way in which video games are perceived; the effect, it can be argued, is subtle. For the millions of Indians playing games such as Empire: Total War or East India Company, their encounter with colonial history is direct and unavoidable, especially given the pervasiveness of postcolonial reactions in everything from academia to day-to-day conversation around them. The ways in which games construct conceptions of spatiality, political systems, ethics, and society are often deeply imbued with a notion of the colonial and therefore also with the questioning of colonialism. This article aims to examine the complexities that the postcolonial undertones in video games bring to the ways in which we read them.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Videogames and Post-Colonialism: Empire Plays Back - Mukherjee, Souvik (Palgrave MacMillan, 2017)
This book focuses on the almost entirely neglected treatment of empire and colonialism in videogames. From its inception in the nineties, Game Studies has kept away from these issues despite the early popularity of videogame franchises such as Civilization and Age of Empire. This book examines the complex ways in which some videogames construct conceptions of spatiality, political systems, ethics and society that are often deeply imbued with colonialism. Moving beyond questions pertaining to European and American gaming cultures, this book addresses issues that relate to a global audience ? including, especially, the millions who play videogames in the formerly colonised countries, seeking to make a timely intervention by creating a larger awareness of global cultural issues in videogame research. Addressing a major gap in Game Studies research, this book will connect to discourses of post-colonial theory at large and thereby, provide another entry-point for this new medium of digital communication into larger Humanities discourses.
Section: ix, 121 pages : illustrations ; 22 cm.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé